To Teach is to Learn - Sara Hussain; Sahar Hussain (University Library System, University of Pittsburgh, 2018)
Learner centered education has been one of the major highlights that has revolutionized the teaching method in every department. While some effort has been made to better implement peer learning into the curriculum in some universities, it remains a vastly underused utility that can be employed both in and out of the classroom. Learning among, and teaching others who are at the same level of education does not only lead to enhanced memory and recall, it also develops critical real-world skills that can enhance the involved individual both professionally and academically. This article is a medical student's perspective on encouraging peer assisted education in the healthcare environment, and a preliminary learning guide for the students who wish to implement this method of education.